Proton-induced direct and indirect damage of plasmid DNA - Vyšín, Luděk; Pachnerová Brabcová, Kateřina; Štěpán, Václav; Moretto-Capelle, Patrick; Bugler, Beatrix; Legube, Gaelle; Cafarelli, Pierre; Casta, Romain; Champeaux, Jean Philippe; Sence, Martine; Vlk, Martin; Wagner, Richard; et al. (Radiation and environmental biophysics, 2015)
Clustered DNA damage induced by 10, 20 and 30 MeV protons in pBR322 plasmid DNA was investigated. Besides determination of strand breaks, additional lesions were detected using base excision repair enzymes. The plasmid was irradiated in dry form, where indirect radiation effects were almost fully suppressed, and in water solution containing only minimal residual radical scavenger. Simultaneous irradiation of the plasmid DNA in the dry form and in the solution demonstrated the contribution of the indirect effect as prevalent. The damage composition slightly differed when comparing the results for liquid and dry samples. The obtained data were also subjected to analysis concerning different methodological approaches, particularly the influence of irradiation geometry, models used for calculation of strand break yields and interpretation of the strand breaks detected with the enzymes. It was shown that these parameters strongly affect the results.
Keywords: Plasmids; Gamma Rays; plazmidy; Models, Biological; protony; Protons; lineární přenos energie; elektroforéza v agarovém gelu; Linear Energy Transfer; enzymy opravy DNA; biologické modely; dvouřetězcové zlomy DNA; poškození DNA; DNA Damage; roztoky; záření gama; Solutions; vztah dávky záření a odpovědi; Electrophoresis, Agar Gel; Dose-Response Relationship, Radiation; DNA Repair Enzymes; DNA Breaks, Double-Stranded